Done deals: venture capitalists tell their stories / edited by Udayan Gupta - Gupta, Udayan (ed.) (Boston, 2000)
This work provides a revealing history of the venture capital industry as told through first-person accounts. It chronicles the industry's beginnings and highlights the differences between America's West and East coast firms. More than thirty leading venture capitalists - from early pioneers such as Eugene Kleiner and Arthur Rock to current top players like Geoff Yang and John Dorrer - reveal insights gleaned from their personal experiences in successful deal-making.
Keywords: Venture capital-Case studies